SEXUAL DEVELOPMENT OF THE TROPICAL SHORT-FINNED EEL Anguilla bicolor bicolor OF THE SEGARA ANAKAN WATERS, CENTRAL JAVA, INDONESIA - Hagi Y. Sugeha; Irwan Jatmiko; Sahri Muhammad (Universitas Gadjah Mada, 2009)
A total of 289 specimens of tropical short-finned ell (Anguilla bicolor bicolor) was collected from Segara Anakan in May, September, October and November 2004. Basic biological information including body weight (BW) and total length (TL), gonad morphology, gonad somatic index (GSI) and eye index (EI) among collecting specimens were examined in order to understand their sexual development. It was found that Anguilla bicolor bicolor from Segara Anakan were greatly varied in body weight (10-900 g) and total length (19-78 cm), suggested their occurred in different like stages (young to adult ell). Based on gonad morphology it was found that sexual development of the species could be separated into four groups namely: female (17.6%), male (48.1%), intersex (32.2%) and developed (2.1%). GSI were 0-3 in female, 1-9 in male, 0-4 in intersex and 2-7 in undeveloped. EI were 3-10 in female, 1-7 in male, 2-8 in intersex and 1-4 in undeveloped. Positive relationship was found between EI and BW and TL of the species in each sexual development, but no correlation between GSI and BW and TL, except for female. Different from temperate eels that bigger in GSI and EI, suggested earlier sexual maturation in the tropical in the temperate.